The Relationship Between Cognitive Flexibility and The Meaning of Life: A Research on The Students of The Faculty of Sport Sciences - Mehmet Cetın; Musab Çağın; Ahmet Dönmez; Nuriye Şeyma Kara (Türk Spor ve Egzersiz Dergisi)
Aim: The aim of this study is to investigate the relationship between cognitive flexibility and meaning of life levels of students studying in the faculty of sports sciences. Method: The research was conducted on 2018-2019 SUBU Faculty of Sport Sciences students using relational screening model. A total of 152 students, 44 females and 108 males, selected by simple sampling, participated in the research. As a data collection tool, “Cognitive Flexibility Scale" developed by Bilgin (2009a), “Meaning of Life Scale” developed by Steger, Frazier, Oishi and Kaler (2006) and translated by Demirdag and Kalafat (2015) and “Personal Information Form” were used. Parametric tests were applied to the data showing normal distribution. Data were analyzed using descriptive statistics, independent groups t-test and Pearson correlation analysis. Findings: The students' cognitive flexibility and meaning of life subscale scores did not differ significantly according to gender and sporting status (p gt; .05). There was no significant relationship between cognitive flexibility scores and age of students (p gt; .05). There was a positive correlation between age and existing meaning (p lt;.05), but there was no significant relationship between age and meaning (p gt; .05). Conclusion: While there was a positive correlation between cognitive flexibility scores and existing meaning (p lt;.05), there was no significant relationship between cognitive flexibility scores and wanted meaning (p gt; .05).